2022
DOI: 10.3390/s22124310
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Diagnosis from DXA Scan and Retinal Images Using Deep Learning

Abstract: Cardiovascular diseases (CVD) are the leading cause of death worldwide. People affected by CVDs may go undiagnosed until the occurrence of a serious heart failure event such as stroke, heart attack, and myocardial infraction. In Qatar, there is a lack of studies focusing on CVD diagnosis based on non-invasive methods such as retinal image or dual-energy X-ray absorptiometry (DXA). In this study, we aimed at diagnosing CVD using a novel approach integrating information from retinal images and DXA data. We consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…While computer vision approaches to extract and analyze DXA scan derived phenotypes are not themselves novel 16,17,29,30 , this work is amongst the first to use this approach on a disease for which diagnosis is primarily radiographic, to demonstrate that having a quantitative endophenotype that captures additional information about variation in disease severity improves power for genomic and epidemiological analysis. Although not based on the imaging data, two novel phenotyping methods leveraging deep learning to impute missing data in the UKB and to generate disease liability scores from binary case-control data in the EHR have shown significant boosts in statistical power for genomic studies 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…While computer vision approaches to extract and analyze DXA scan derived phenotypes are not themselves novel 16,17,29,30 , this work is amongst the first to use this approach on a disease for which diagnosis is primarily radiographic, to demonstrate that having a quantitative endophenotype that captures additional information about variation in disease severity improves power for genomic and epidemiological analysis. Although not based on the imaging data, two novel phenotyping methods leveraging deep learning to impute missing data in the UKB and to generate disease liability scores from binary case-control data in the EHR have shown significant boosts in statistical power for genomic studies 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one study has reported an excellent algorithm performance in CVD detection after integrating fundus images and dual-energy X-ray absorptiometry scans. 108 Second, the studies cited above showed good predicting performance of CVD risk factors, biomarkers, and other CVD-related conditions. Nevertheless, the studies did not adequately evaluate the added diagnostic value of the DL models by directly comparing the algorithms with the existing CVD risk assessment tools or stratification methods; this may impact the perceived applicability and acceptance by patients, regulatory agencies, and other healthcare providers involved in managing CVD.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…To the best of our knowledge, only one study has reported an excellent algorithm performance in CVD detection after integrating fundus images and dual-energy X-ray absorptiometry scans. 108…”
Section: Implications For Clinical Practice and Integrationmentioning
confidence: 99%
“…It was found that the accuracy of the classification model trained on retina images alone and DXA data alone was 75.6% and 77.4%, respectively, whereas the introduction of the multimodal model improved accuracy to 78.3%. These noninvasive combination methods provide a new approach to the early detection of CVDs 92 …”
Section: Application Of Ai Using Ocular Images For Systemic Diseases ...mentioning
confidence: 99%
“…These noninvasive combination methods provide a new approach to the early detection of CVDs. 92 The analysis of CVDs through AI-assisted ophthalmic imaging lags notably behind its application in neurological disorders. Current analyses primarily focus on fundus imaging, where accuracy in disease classification and severity assessment falls within the range of 0.7 to 0.9, matching expert-level evaluations in some studies.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%